ANALISIS STRUKTUR DAN NILAI-NILAI MORAL YANG TERKANDUNG DALAM CERPEN TEN MADE TODOKE KARYA YOSHIDA GENJIRO - Lado, Susana Fitriana; Fadli, Zaki Ainul; Rahmah, Yuliani (Program Studi Sastra Jepang, Fakultas Ilmu Budaya, Universitas Diponegoro, 2016)
The sequence of this thesis are: first the writer collects the references and analyzes the data. Then, she obtained the data from Anthology of Japanese children's literature's book. The problems that will be studied in this thesis are intrinsicelements and the moral values contained in Ten Made Todoke Yoshida Genjiro’s short story. This study uses structural method. The method is used to analyze the intrinsicelements that lead to moral values of the story. It makes the writer easier to analyze the moral values of story. The intrinsic elements that will be discussed in this thesis are theme, character, plot, setting, point of view, and the message of story.